Computer Literacy Skills as a Determinant of Electronic Reference Sources Utilization among Selected Secondary School Students in Ado-Odo Ota Local Government, Ogun State, Nigeria - Lateef, Elizabeth Bukunola; Ozonuwe, Opene Sunday; Farukuoye, Adesanmi Matthew (International Journal of Knowledge Content Development & Technology, 2024)
The study investigated computer literacy skills as a determinant of electronic reference sources utilization among selected secondary school students in Ado-Odo Ota Local Government, Ogun State, Nigeria. Four specific objectives with conforming research questions guided the study. Descriptive survey research design was adopted for the study. The population of the study comprises of SSS3 students of the three selected Community Secondary Schools in Ado Odo Ota. A sample size of 150 was used for the study. The instrument for data collection was a self-developed structured questionnaire. Data collected was analyzed using frequency and percentages. Findings of the study revealed that majority of secondary school students were not aware of the availability of electronic reference sources. It also revealed that the level of their computer literacy skills was below average. Majority of them have never used computer before and the few of them that have used computer before used it in their homes, their friend’s homes or in the cyber café. It was found that lack of formal training on the use of electronic reference sources, lack of access to computer, lack of awareness of availability of electronic reference sources, lack of funds for internet subscriptions, over dependency on printed reference sources and lack of motivation to use electronic reference sources were the major hindrances to the use of electronic reference sources among secondary school students. It was recommended that the school librarians and teachers should play a role in creating awareness among secondary school students about the availability of online/ electronic reference sources among others.